Studi Komparatif Indikator Toleransi Beragama di Indonesia dalam Perspektif Teori Multikultural Barat dan Pendidikan Agama Islam: Comparative Study of Religious Tolerance Indicators in Indonesia from the Perspective of Western Multicultural Theory and Islamic Religious Education - Rosidin (TA'LIMUNA: Jurnal Pendidikan Islam, 2024)
The low index of religious tolerance in Indonesia is still a problem that requires a solution. This article uses a qualitative approach and a type of literature study. The data studied is secondary data that is relevant to the themes of religious tolerance, multiculturalism and Islamic religious education. Then it was analyzed through data condensation, data display, and conclusion, until the following findings were obtained: 1) The establishment of non-Muslim places of worship in the perspective of Western multiculturalism related to integration (acceptance) such as in Kampung Sawah, Bekasi; and conflict (rejection) such as in Ciketing Asem, Bekasi. In Islamic religious education, there are different opinions, namely Haram (forbidden), Halal (permissible), Wajib (obligatory) and Tafshil (conditional). 2) The election of non-Muslim leaders in the perspective of Western multiculturalism is related to the principle of equal rights to be elected and hold power. In Islamic religious education, there are differences of opinion, namely firmly rejecting, accepting unconditionally, and accepting with certain conditions. 3) Organizing non-Muslim religious events in public spaces from the perspective of Western multiculturalism related to conflict transformation, namely turning violence into non-violence. In Islamic religious education, it is forbidden for Muslims to participate in religious ceremonies and wear non-Muslim religious attributes. 4) Non-Muslims are buried in public cemeteries in the perspective of Western multiculturalism regarding mechanical social solidarity which prioritizes repressive laws, and organic solidarity which prioritizes restitutive laws. In Islamic religious education, non-Muslims cannot be buried in the same place as Muslims, unless it is an emergency. Rendahnya indeks toleransi beragama di Indonesia masih menjadi problem yang membutuhkan solusi. Artikel ini memakai pendekatan kualitatif dan jenis studi pustaka. Data yang diteliti adalah data sekunder yang relevan dengan tema toleransi beragama, multikulturalisme Barat dan Pendidikan Agama Islam (PAI). Lalu dianalisis melalui reduksi dan kondensasi data, penyajian data, dan penarikan kesimpulan, hingga diperoleh temuan berikut: 1) Pendirian rumah ibadah non-Muslim dalam perspektif multikulturalisme Barat terkait integrasi (penerimaan) seperti di Kampung Sawah, Bekasi; dan konflik (penolakan) seperti di Ciketing Asem, Bekasi. Dalam perspektif PAI, terdapat perbedaan pendapat, yaitu Haram, Halal mutlak, Wajib dan Tafshil (diperinci) sesuai kondisi. 2) Pemilihan pemimpin non-Muslim dalam perspektif multikulturalisme Barat terkait prinsip kesetaraan hak untuk dipilih dan memegang kekuasaan. Dalam perspektif PAI, terjadi perbedaan pendapat, yaitu tegas menolak, menerima tanpa syarat, dan menerima dengan syarat tertentu. 3) Penyelenggaraan acara keagamaan non-Muslim di ruang publik dalam perspektif multikulturalisme Barat terkait transformasi konflik, yaitu mengganti kekerasan menjadi anti kekerasan. Dalam perspektif PAI, umat muslim haram mengikuti upacara keagamaan dan memakai atribut keagamaan non-muslim. 4) Non-Muslim dimakamkan di Tempat Pemakaman Umum dalam perspektif multikulturalisme Barat terkait solidaritas sosial mekanik yang mengedepankan hukum represif, dan solidaritas organik yang mengedepankan hukum restitutif. Dalam perspektif PAI, non-muslim tidak boleh dimakamkan satu lokasi dengan orang muslim, kecuali darurat. Kata Kunci: Studi Komparatif, Toleransi Beragama, Multikulturalisme Barat, Pendidikan Agama Islam (PAI)